2017
DOI: 10.1089/cmb.2016.0154
|View full text |Cite
|
Sign up to set email alerts
|

EvOligo: A Novel Software to Design and Group Libraries of Oligonucleotides Applicable for Nucleic Acid-Based Experiments

Abstract: Experimental methods based on DNA and RNA hybridization, such as multiplex polymerase chain reaction, multiplex ligation-dependent probe amplification, or microarray analysis, require the use of mixtures of multiple oligonucleotides (primers or probes) in a single test tube. To provide an optimal reaction environment, minimal self- and cross-hybridization must be achieved among these oligonucleotides. To address this problem, we developed EvOligo, which is a software package that provides the means to design a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In these assays, in addition to the above-characterized three pairs of substrates, we also used two short RNAs that were differentially base paired with guide RNA, R21. One 21-nt RNA, called "mR21", was designed using EvOligo software computation core [26] to form a double-mismatched duplex with R21, that mimicked a miRNA duplex. The other 21-nt RNA, called "cR21", formed a perfect duplex with R21 that mimicked an siRNA duplex (based on Ameres et al [21]).…”
Section: Influence Of the Rna Structure On The Annealing Activity Of mentioning
confidence: 99%
“…In these assays, in addition to the above-characterized three pairs of substrates, we also used two short RNAs that were differentially base paired with guide RNA, R21. One 21-nt RNA, called "mR21", was designed using EvOligo software computation core [26] to form a double-mismatched duplex with R21, that mimicked a miRNA duplex. The other 21-nt RNA, called "cR21", formed a perfect duplex with R21 that mimicked an siRNA duplex (based on Ameres et al [21]).…”
Section: Influence Of the Rna Structure On The Annealing Activity Of mentioning
confidence: 99%
“…The lower (more negative) the value, the stronger the interaction between the oligonucleotides. Using EvOligo ( 57 ) we calculated ΔGs for the duplexes formed by unmodified AL-ASOs and their respective miR-181a precursors, as well as AL-ASOs and other pre-miRNAs (potential off-targets identified within known X. laevis precursors). We found that theoretical Δ G for AL:pre-miR-181a-1/-2 duplexes were all below –21 kcal/mol ( Supplementary Table S1 ), which was at least 1.5 times lower than for AL-ASOs pairs with any other pre-miRNA.…”
Section: Resultsmentioning
confidence: 99%
“…One of the input PTS from the last alignment round was selected and converted into reverse-complement to obtain a control oligomer sequence (Ctrl and h Ctrl). The self- and cross-hybridization free Gibbs energies of all designed oligomers were calculated using EvOligo ( 57 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, homologous sequences between FPs were preferentially selected as the cutting sites to increase the fragment recombination. Theoretically, the total reassemble clones were A 360 20 + A 450 25 = 1.08 × 10 66 , provided that all of the sections can be recombined freely. Actually, the chances of premature reassembled products, invalid combination products, and wildtype recombination reduced the final obtained clones.…”
Section: Resultsmentioning
confidence: 99%
“…Oligonucleotide design for synthesis was the key part of this study. Although several algorithms have now been made to design combinatorial oligonucleotide pools, few computationally designed oligonucleotide pools have been characterized experimentally. DNAworks algorithm was used as it has advantages in the balance of highly homogeneous melting temperatures, minimization of hairpin formation, ease of handling, and experimental verification . Here, 18 widely used FPs were selected as input templates for computer-based oligonucleotide design, and thermally balanced oligonucleotides were massively synthesized in parallel in our light-directed microfluidic arrays.…”
Section: Introductionmentioning
confidence: 99%